Hinduism Theological Study On Albinism Phenomenon - I Wayan Gama; Kadek Aria Prima Dewi PF (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2020)
This study aims to investigate: 1) the views of the Pucang community about albinism, 2) the inheritance pattern of albinism, 3) preventive efforts to prevent the spread of albinism, and 4) the Hinduism theology related to albinism among the Pucang community. The methods used in data collection were interviews, observation, documentation, and literature review. The collected data was analyzed descriptively. There are 9 cases of people with albinism in Desa Adat Pucang. Albino sufferers were born from parents who are close relatives. The people of Desa Adat Pucang believe that albino sufferers were descended from Bethara Pancering Akasa and assume that albino sufferers might be sacrificed as caru(ceremonial offering) during the Panca Bali Krama and Eka Dasa Ludra ceremonies in Besakih Temple. Preventive efforts that can be done to decrease the number of albinism cases are including: 1) avoiding close-family marriages, 2) making ‘awig-awig’ (rules and regulations) which contains an appeal that close-family marriages are unfortunate and, 3) genetic counseling for couples who will be married and have been married , and 4) expanding the social interaction and education of Desa Adat Pucang in order to broaden the insights about albinism.